Baby Blues from a Quranic Perspective - Irma Indriani; Nurlaila Nurlaila (FiTUA: JURNAL STUDI ISLAM, 2026)
The phenomenon of baby blues is a psychological condition commonly experienced by mothers after childbirth, characterized by feelings of sadness, anxiety, irritability, and emotional exhaustion. This article aims to examine the baby blues phenomenon from the perspective of the Qur'an by analyzing the story of Maryam in Surah Maryam, verses 16–26. The study employs a thematic interpretation (tafsir maudhū'ī) combined with a religious-psychological approach to explore the meaning and psychological relevance of Maryam's story in relation to the mental health conditions of contemporary mothers. The findings indicate that Maryam experienced severe psychological pressure during pregnancy, childbirth, and the postpartum period, as reflected in her verbal and emotional expressions. The Qur'an, through this narrative, conveys significant messages about empathy, spiritual support, and the importance of social assistance for women undergoing psychological distress after giving birth. This study contributes to the discourse on Islamic psychology by proposing a Qur'anic-based reflective framework that integrates spiritual, emotional, and social dimensions in addressing maternal mental health.